Exploring interaction design opportunities for remote robotic services - Boström, Cecilia; Mudumby, Varuna (My University, 2015)
There is an emerging field within the robotics industry, where remote robotic services serve to aid people working in industrial factory plants by providing fast and proactive maintenance information. ABB Robotics seeked to accomplish these things by launching a remote service system called MyRobot. Customers bought the MyRobot service as part of a larger service agreement. It did however not meet the expectations ABB had, as several customers chose not renew their service agreements after expiration. The main reason being that MyRobot did not meet customers needs. This thesis proposes an alternative remote service solution using interaction design methods to meet user needs. Robot manufacturers and robot end-customers were interviewed and observed within their work environments to gain an understanding of their daily activities. In total, four different robot end-customer companies were studied, the smallest owning two robots and the biggest approximalely two hundred. The information obtained from the empirical data colletion was analyzed and together with a brainstorming session, the data formed requirements for a new system called Pythia. Pythia is designed as a customizable system that incorporates all vital information in one place. The prototype was tested on all studied end-customers and the results suggest that the system have big potential for bigger companies with robot expertise. The current robot market is conservative and many people do not realize the need and potential of using remote services. Nevertheless, there are endless possibilities yet to be explored.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction